New Vocabulary for Bacterial Communication. (16th December 2019) - Tobias, Nicholas J.; Brehm, Jannis; Kresovic, Darko; Brameyer, Sophie; Bode, Helge B.; Heermann, Ralf
Abstract: Quorum sensing (QS) is widely accepted as a procedure that bacteria use to converse. However, prevailing thinking places acyl homoserine lactones (AHLs) at the forefront of this communication pathway in Gram‐negative bacteria. With the advent of high‐throughput genomics and the subsequent influx of bacterial genomes, bioinformatics analysis has determined that the genes encoding AHL biosynthesis, originally discovered to be indispensable for QS (LuxI‐like proteins and homologues), are often absent in QS‐capable bacteria. Instead, the sensing protein (LuxR‐like proteins) is present with an apparent inability to produce any outgoing AHL signal. Recently, several signals for these LuxR solos have been identified. Herein, advances in the field of QS are discussed, with a particular focus on recent research in the field of bacterial cell–cell communication. Abstract : It's good to talk ! It is recognised that bacteria communicate through small diffusible molecules in a process termed quorum sensing, which involves regulating group‐mediated behaviour. New bacterial communication systems and their chemical signals are reviewed to expand the available bacterial vocabulary.